2022
DOI: 10.3390/lubricants10040055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Base Oil and Thickener on Texture and Flow of Lubricating Greases: Insights from Bulk Rheometry, Optical Microrheology and Electron Microscopy

Abstract: The structure and flow behavior of lubricating greases depend on the base oil and the type and concentration of the dissolved thickener. In this study, the linear viscoelastic properties of greases were characterized by combining oscillatory shear and squeeze flow covering a broad frequency range (0.1–105 rad s−1). Multiple-particle tracking (MPT) microrheology and scanning electron microscopy (SEM) provided further insight into local viscoelastic properties and sample structure on a submicron-length scale. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The grease is non-Newtonian liquid, classified as thixotropic liquid. Under the influence of shear forces, its internal structure is destroyed and viscosity is reduced [ 33 ]. Oil is separated as a result of breaking the bonds of the cross-linker, which enables better lubrication.…”
Section: Resultsmentioning
confidence: 99%
“…The grease is non-Newtonian liquid, classified as thixotropic liquid. Under the influence of shear forces, its internal structure is destroyed and viscosity is reduced [ 33 ]. Oil is separated as a result of breaking the bonds of the cross-linker, which enables better lubrication.…”
Section: Resultsmentioning
confidence: 99%
“…In the range of yield stress, grease viscosity decreases rapidly with increasing shear rate stress, and in the high shear rate range, viscosity asymptotically approaches a value like that of oil. These changes are influenced by changes in the grease thickener network [26], so the flow differs from grease to grease even at the same shear rate. In addition, Abdulrazaq et al [27] have analyzed viscoelastic fluids, such as grease, during elongational deformation and found that the yield stress threshold, surface tension coefficient, and viscosity ratio in the material during elongation affect the elongation characteristics.…”
Section: Mechanism Of Grease Reduction On Lubricated Surfacesmentioning
confidence: 99%